Regional economic development in the lens of the dilemma between growth poles approach and the balanced growth theory during the Francoist regime - Varela Vázquez, Pedro; de Francisco, Carlos (Iberian Journal of the History of Economic Thought, 2024)
Regional economic development gained increasing relevance in European policy agendas after the Second World War, especially under the implementation of indicative planning. Likewise, a lively debate arose between the growth poles approach and the balanced growth theory. The main aim of this paper is to analyse this dilemma mainly through contributions from the Revista de Economía de Galicia (Galician Economic Review), as a representative observatory of this controversial discussion in the Francoist regime. National and international contributions underlined the positive potential effects of fostering an upgrading process of traditional sectors as a way of enhancing balanced and endogenous growth..